A comparison of learning outcomes from two poverty simulation experiences. Issue 3 (7th January 2021) - Sanko, Jill S.; Matsuda, Yui; Salani, Deborah; Tran, Lien; Reaves, Regine; Gerber, Kathryn
Abstract: Objectives: Five nationally representative U.S. federal data sources consistently showed the link between poverty and poor health outcomes. To determine the modality effective in teaching students about poverty and health, this study compared the attitudes toward poverty of students participating in the Community Action Poverty Simulation (CAPS) and the poverty table‐top simulation (Dwell™). Methods: In this quasi‐experimental study, undergraduate and graduate nursing students and physical therapy students participated in either CAPS or a table‐top simulation (TTS) depending on their semester of enrollment in the relevant course. The Undergraduate Perception of Poverty Tracking Survey (UPPTS) was administered before and after each simulation. Results: The analysis included 118 matched pairs. Using MANOVA tests, the authors found no group difference in the overall change of attitude after the simulations ( p  = .232). However, by the subscale analyses, TTS significantly increased students' willingness to help ( p  = .008, η 2  = 0.058) and their empathy toward those living in poverty ( p  = .039, η 2  = 0.039). Conclusion: TTS participants had more elements of improvement, but both modalities were found to change participants' attitudes.